Data accompanying "Drone data reveal heterogeneity in tundra greenness and phenology not captured by satellites" - Assmann, Jakob J.; Myers-Smith, Isla H.; Kerby, Jeffrey T.; Cunliffe, Andrew M.; Daskalova, Gergana (Zenodo, 2020)
This dataset contains the spatial data underlying the statistical analysis in: Assmann et al. (in press) - Drone data reveal heterogeneity in tundra greenness and phenology not captured by satellites Together with the code and tabular data contained in https://github.com/jakobjassmann/qhi_phen_ts/ the data in this repository are required to reproduce the figures, tables and statistics reported in the manuscript. This dataset consists of two components: Multispectral drone observations from the growing seasons 2016 and 2017 for 8 study plots on Qikiqtaruk - Herschel Island in Canada collected with Parrot Sequioa sensors (62 sets of multispectral orhomosaics in total). Post-porcessed Sentinel-2 MSI L2A scenes covering the same 8 study plots, including all scenes for which the area of the plots and their immediate surroundings were cloud free between May and September in 2016 and 2017. ----------------------------------------------------------------------------------------------------------------- Citation : Jakob J. Assmann, Isla H. Myers-Smith, Jeffrey T. Kerby, Andrew M. Cunliffe and Gergana N. Daskalova. In press . Drone data reveal heterogeneity in tundra greenness and phenology not captured by satellites. https://doi.org/10.32942/osf.io/tqekn Legal notice: This dataset contains modified Copernicus Sentinel [2016, 2017] data. Acknowledgements (from the manuscript): We would like to thank the Team Shrub field crews of the 2016 and 2017 field seasons for their hard work and effort invested in collecting the data presented in this research, this includes Will Palmer, Santeri Lehtonen, Callum Tyler, Sandra Angers-Blondin and Haydn Thomas. Furthermore, we would like to thank Tom Wade and Simon Gibson-Poole from the University of Edinburgh Airborne GeoSciences Facility, as well as Chris McLellan and Andrew Gray from the NERC Field Spectroscopy Facility for their support in our drone endeavours. We also want to express our gratitude to Ally Phillimore, Ed Midchard, Toke Høye and two anonymous reviewers for providing feedback on earlier versions of this manuscript. Lastly, JJA would like to thank IMS, Ally Phillimore and Richard Ennos for academic mentorship throughout his PhD. We thank the Herschel Island—Qikiqtaruk Territorial Park Team and Yukon Government for providing logistical support for our field research on Qikiqtaruk including: Richard Gordon, Cameron Eckert and the park rangers Edward McLeod, Sam McLeod, Ricky Joe, Paden Lennie and Shane Goosen. We thank the research group of Hugues Lantuit at the Alfred Wegener Institute and the Aurora Research Institute for logistical support. Research permits include Yukon Researcher and Explorer permits (16-48S&E and 17-42S&E) and Yukon Parks Research permits (RE-Inu-02-16 and 17-RE-HI-02). All airborne activities were licensed under the Transport Canada special flight operations certificates ATS 16-17-00008441 RDIMS 11956834 (2016) and ATS 16-17-00072213 RDIMS 12929481 (2017). Funding for this research was provided by NERC through the ShrubTundra standard grant (NE/M016323/1), a NERC E3 Doctoral Training Partnership PhD studentship for Jakob Assmann (NE/L002558/1), a research grant from the National Geographic Society (CP-061R-17), a Parrot Climate Innovation Grant, the Aarhus University Research Foundation, and the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement (754513) for Jeffrey Kerby, a NERC support case for use of the NERC Field Spectroscopy Facility (738.1115), equipment loans from the University of Edinburgh Airborne GeoSciences Facility and the NERC Geophysical Equipment Facility (GEF 1063 and 1069). Finally, we would like to thank the Inuvialuit people for the opportunity to conduct research in the Inuvialuit Settlement Region.